Vitamin D and adrenal gland: Myth or reality? A systematic review - Al Refaie, Antonella; Baldassini, Leonardo; De Vita, Michela; Gonnelli, Stefano; Caffarelli, Carla (Frontiers in Endocrinology, 2022)
In recent years, vitamin D has become the protagonist in many studies. From cardiology to oncology the spotlight was on this vitamin. While in the past it was considered for its important role in phospho-calcium metabolism and skeletal disorders; today by studying it better, thousands of scenarios and facets have opened up on this vitamin which is actually a hormone in all respects. There are authoritative studies that demonstrate its activity in vitro and in vivo on: carcinogenesis, inflammation, autoimmunity and endocrinopathies. Its role has been studied in type 1 and type 2 diabetes mellitus, in Hashimoto or Graves’ thyroiditis and even in adrenal gland diseases. In fact, there are sev-eral studies that demonstrate the possible correlations between vitamin D and: Addison’s disease, Cushing disease, hyperaldosteronism or adrenocortical tumors. Moreover this fascinating hormone and adrenal gland even seem to be deeply connected by common genetic path-ways. This review aimed to analyze the works that have tried to study the possible influence of vitamin D on adrenal diseases. In this review we analyze the works that have tried to study the possible influence of vita-min D on adrenal disease.